What influences adolescent girls' decision-making regarding contraceptive methods use and childbearing? a qualitative exploratory study in Rangpur District, Bangladesh - Shahabuddin, A. S. M.; Nöstlinger, Christiana; Delvaux, Thérèse; Sarker, Malabika; Bardají, Azucena; De Brouwere, Vincent; E. W. Broerse, Jacqueline (© 2016 Public Library of Science, 2016)
This article was published in PLoS ONE [© 2016 Public Library of Science] and the definite version is available at: http://journals.plos.org/plosone/article?id=10.1371/journal.pone.0157664